BROADCASTING NITROGEN IN NO-TILLAGE OF SUNFLOWER: II PLANT MORPHOLOGY AND DRY MATTER PARTITION - BRUGINSKI, Denise Heimbecker; PISSAIA, Amir (Scientia Agraria, 2002)
The present work, carried-out in the agricultural year of 1998/99, had as an objective to evaluate the effect of different levels of nitrogen in covering in the sunflower cultivation (Helianthus annuus L.) in notillage system about morphologic characteristics and dry matter partition. The experiment was driven at Fazenda Agripastos, in Palmeira, region of Campos Gerais, Paraná, in a red-yellow argissol, cultivated in no-tillage system since 1976. The experimental design used was the randomized blocks with four repetitions. The tested treatments were: doses of nitrogen (0, 25, 50, 75, 100 and 125 kg.ha-1), in the urea form, applied in covering when the plants were met in the V8 stage. For the evaluations five plants were sampled in an experimental unit in V8, V17, R1, R5.5 and R7 stages, to evaluated the variables: total number of leaves, height of the plant, diameter of the stem, area to foliate, foliate area index, diameter of the capitulum and matter partition drought. The nitrogen fertilization in covering, in the conditions of the experiment, didnt present any changing in the partition of dry matter and the morphologic characteristics of the sunflower.